Modeling the conditional volatility asymmetry of business cycles in four OECD countries: A multivariate GARCH approach - Ho, K.-Y. (2014)
MODSIM 2011 - 19th International Congress on Modelling and Simulation - Sustaining Our Future: Understanding and Living with Uncertainty